Midface Fractures I - Louis, Matthew; Agrawal, Nikhil; Kaufman, Matthew; Truong, Tuan A. (Seminars in Plastic Surgery, 2017)
Facial fractures are a common source of emergency department consultations for the plastic surgeon. A working understanding of evaluation, assessment, management, and prevention of further injury when dealing with these fractures is vital. This two-part series detailing the management of midface fractures serves as a guide for the appropriate workup and management of the wide variety of fracture patterns that are commonly encountered.
Keywords: midface fractures; naso-orbital ethmoid fractures; nasal fractures; zygoma fractures; orbital fractures